Limit conditions for the use of single stack in residential building sanitary sewer systems - Fernandes, Vera Maria Cartana (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents some limit conditions for the use of single stack in residential building sanitary sewer systems, through the evaluation of the ventilation conditions inside those systems. Tests were performed in prototypes of building sanitary sewer systems, considering Brazilian building typologies, in which the pressures in different points of the systems were evaluated, as well as the behaviour of seal traps. The prototypes were tested with several sanitary appliance flow arrangements and different diameters, all of them having only primary ventilation. The aim of this study is to provide building drainage system designers with safer conditions for using that type of ventilation system, which was introduced in the latest revision of NBR 8160 – Building Sanitary Sewer Systems – Design and execution – Procedures.